Transient abnormal myelopoiesis with extramedullary involvement in a down syndrome preemie leading to an unresponsive course despite chemotherapy - Saroja Devi Geetha; Ram Singh; Meira Shaham; Ninette Cohen; Kristin Sticco (Leukemia Research Reports, 2023)
Introduction: Transient abnormal myelopoiesis (TAM) is a transient, clonal myeloproliferative disorder unique to Down Syndrome (DS) babies. It is characterized by increased peripheral blasts and presence of GATA1 mutation. The clinical spectrum ranges from jaundice and hepatosplenomegaly to multi-organ failure and death. Here we present a case of a premature baby with DS diagnosed to have TAM with extramedullary involvement at birth who had a fatal outcome. Case report: A 30.3-week-old female fetus with DS had leukocytosis (WBC: 187.82 K/uL) with neutrophilia (ANC 27.65 K/uL), macrocytic anemia (RBC: 2.41 m/uL, Hb 8.8 g/dL, MCV 108.3, MCH 36.5, MCHC 33.7) and thrombocytosis (platelet count 361 K/uL) at birth. Liver panels demonstrated normal bilirubin levels with elevated liver enzymes (AST = 239 U/L, ALT = 216 U/L). Results: Peripheral smear showed marked leukocytosis with increased blasts (70%), nucleated RBCs, giant platelets, and megakaryocytic elements. Flow cytometry demonstrated two populations of cells: 20% myeloblasts and 26% dim CD45 CD34- cells. GATA1 mutation was present. Based on these findings a diagnosis of TAM with extramedullary hematopoiesis was made. She received two cycles of cytarabine chemotherapy. Though her WBC levels reached a low of 18.93 K/uL, she developed multi-organ failure, eventually leading to death on day 45. Discussion: TAM is a transient condition resulting in disease resolution in around 80% of cases. Death is reported in 10% of cases. Risk factors associated with early death include prematurity, hyperleukocytosis, elevated bilirubin levels. Management of high-risk babies with chemotherapy is recommended to improve survival.